Innovation in Dental Health Education with Card Towards Healthy Teeth (KMGS) to Increase the Knowledge and Skills of Mothers Under Five in the Prevention of Caries in Jabungan Village, Semarang - Wiradona, Irmanita; Wiyatini, Tri; Yodong, Yodong; Prasko, Prasko (Jurusan Kesehatan Gigi, Poltekkes Kemenkes Semarang, 2025)
Dental and oral health problems are still a challenge in Indonesia, especially in early childhood. Based on the 2018 Riskesdas, in the city of Semarang, 37.20% of children experienced cavities, while the prevalence of caries in children aged 3-4 years reached 81.5%. The DMF-T value in that age group was 4.9 and increased to 6.7 at the age of 5, which is very high. This condition confirms the importance of the role of parents, especially mothers, in early prevention. This condition emphasizes the importance of the involvement of parents, especially mothers, in early prevention. Posyandu has indeed provided education, but the use of the Card for Healthy Teeth (KMGS) is still limited and has not fully involved the active role of parents. This study aims to analyze the influence of KMGS as an educational medium for mothers under five in improving knowledge and skills to maintain children's dental health. The method used was a quasi-experiment with a pretest-posttest design on 15 mothers under five at the Posyandu of Jabungan Village with data analysis using the Wilcoxon test. The results showed a significant increase in the knowledge (p=0.014) and skills (p=0.007) of mothers after being given the intervention. Thus, the use of KMGS is proven to improve the knowledge and skills of mothers in maintaining children's dental health